Exploring Teachers’ Beliefs in Teaching Grammar - ELISHA NURUSUS*; ARSHAD ABDUL SAMAD; SHARIFAH ZAINAB SYED ABDUL RAHMAN; NOOREEN NOORDIN; JURIDAH MD. RASHID (The English Teacher, 2015)
Teachers’ beliefs can play an important role in their decision-making regarding the type of materials, activities and instruction they will use in their lessons. At the same time, without conviction in their beliefs about how students learn, it is difficult to imagine teachers being effective in their teaching regardless of the approach they take. Most English language teachers have their own set of personal beliefs of grammar teaching and how grammar should be taught. The years of teaching experience a teacher has can easily shape such beliefs. This paper looks at teachers’ beliefs using the data collected from a survey administered to 345 English language teachers in secondary schools in two states in Malaysia. A self-developed instrument modeled after Ellis (1998) was used in the study. The instrument looked at four aspects of grammar instruction in the classroom – input, explicit L2 knowledge, student output and error correction. The data were analyzed according to how teachers with varying years of teaching experience viewed the importance of each of these aspects of grammar instruction. The results indicated a number of interesting points which can help inform schools, teachers and other interested parties on how to plan for and present grammar in the classroom.
Keywords: teacher education, beliefs, grammar instruction